2023
DOI: 10.3389/fphy.2023.1142136
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of low-radioactive high-purity enriched 100MoO3 powder for AMoRE-II experiment

Abstract: This paper describes preparing radiopure molybdenum trioxide powder enriched with Mo-100 isotope for the AMoRE-II experiment. AMoRE-II, the second phase of the AMoRE experiments, will search for the neutrinoless double-beta decay (0νDBD) of the 100Mo isotope using over 100 kg of 100Mo embedded in 200 kg of ultra-pure Li2100MoO4 bolometric crystals. Efficient purification technology was developed and adapted to purify 100MoO3 powder with a 5 kg per month production capacity. Based on the ICP-MS analysis of puri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…These crystals had a yellowish color and were unsuitable for use in the experiment. The coloration of the crystals could not be caused by impurities from molybdenum since the molybdenum oxide was purified at CUP, and its purity was confirmed [27]. With extensive ICP-MS and HPGe analysis of Li 2 CO 3, we did not find any contaminants at the levels over a few ppm, which may explain the yellowish color of the crystals.…”
Section: Radioassay Of Commercially Available Powdersmentioning
confidence: 67%
See 1 more Smart Citation
“…These crystals had a yellowish color and were unsuitable for use in the experiment. The coloration of the crystals could not be caused by impurities from molybdenum since the molybdenum oxide was purified at CUP, and its purity was confirmed [27]. With extensive ICP-MS and HPGe analysis of Li 2 CO 3, we did not find any contaminants at the levels over a few ppm, which may explain the yellowish color of the crystals.…”
Section: Radioassay Of Commercially Available Powdersmentioning
confidence: 67%
“…About 180 kg of molybdenum trioxide ( 100 MoO 3 ), enriched in the 100 Mo isotope, and 150 kg of lithium carbonate are used as precursors for the crystal synthesis. The procedure for the purification of enriched 100 MoO 3 for AMoRE-II was finalized and carried out at the CUP facility [27]. This study was focused on understanding the initial Li 2 CO 3 purity required for AMoRE-II crystal synthesis with both techniques and what purity levels are commercially available in the market.…”
Section: Introductionmentioning
confidence: 99%
“…All the crystals needed for the second stage of AMoRE-II are expected to be ready by mid 2025. The raw materials for the crystal growing, MoO 3 and Li 2 CO 3 powder, have been being purified at CUP/IBS for reducing radioactivity [5].…”
Section: Pos(taup2023)214mentioning
confidence: 99%
“…Calcium-based and carbonate-based carriers were selected for Ra removal. Our previous studies demonstrated that the CMO-based carrier [14,18] efficiently separates thorium and radium. After the co-precipitate was filtered out using the PTFE membrane filter, the lithium nitrate solution was analyzed with ICP-MS at the CUP (Table 2).…”
Section: Lithium Nitrate Purification Via Co-precipitationmentioning
confidence: 99%
“…Bolometers for AMoRE-II have been produced with conventional [12] and low-temperature gradient Czochralski [13] techniques. To ensure the radiopurity and uniformity of the synthesized crystals despite the crystallization technique used, high-purity and low-radioactive initial materials, namely, 100 MoO 3 [14] and Li 2 CO 3 powders, are required. The current study mainly focuses on Li 2 CO 3 preparation for the AMoRE project.…”
Section: Introductionmentioning
confidence: 99%